2017
DOI: 10.1016/j.athoracsur.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome and Prognostic Stratification for Pulmonary Metastasis From Colorectal Cancer

Abstract: Metastasectomy of PM from colorectal cancer was associated with a favorable prognosis. Patients could be classified into three risk groups using five prognostic factors. This grouping may be useful for identifying an optimal treatment strategy according to risk in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 17 publications
4
57
3
2
Order By: Relevance
“…While surgery remains the gold standard for resectable oligometastasis from CRC, local control outcomes in vivo 34: 2991-2996 (2020) in recent reports of SBRT have closely approached those of surgery. Several investigators have reported 2-year LC and OS rates of 53% to 100% and 68% to 92%, respectively, in their SBRT series (14-19), which were almost comparable to those of surgery (20,21). In the present study, we treated patients with SBRT using the Cyberknife ® system, and report 2-year rates of 65.8% and 88.6% for LC and OS, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…While surgery remains the gold standard for resectable oligometastasis from CRC, local control outcomes in vivo 34: 2991-2996 (2020) in recent reports of SBRT have closely approached those of surgery. Several investigators have reported 2-year LC and OS rates of 53% to 100% and 68% to 92%, respectively, in their SBRT series (14-19), which were almost comparable to those of surgery (20,21). In the present study, we treated patients with SBRT using the Cyberknife ® system, and report 2-year rates of 65.8% and 88.6% for LC and OS, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Less commonly reported criteria include LN involvement, DFI and number of metastases. When these criteria are achieved, the tail or flattening of OS curves in contemporary reports include colorectal (OS 20-52% at 7-9 yrs) [13,14], renal cell carcinoma (OS 33% 7 yrs) [15], melanoma (OS 14% 10 yr) [16], soft tissue sarcoma (OS 11-23% 7-11 yrs) [17,18], head and neck squamous cell cancer (OS 18% 13 yrs) [19], breast cancer (OS 40% at 18 yrs) [20] and hepatocellular carcinoma (OS 38% over 10 yrs) [21]. Is PM associated with prolonged survival (without cure)?…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pulmonary metastasectomy has evolved for other cancers with synchronous or metachronous metastatic disease, such as colorectal adenocarcinoma, with a demonstrated survival benefit [ 12 15 ]. In PDAC, Arnaoutakis et al reported that, in patients with isolated PM from PDAC, median cumulative survival was significantly improved in the pulmonary metastasectomy group compared with the chemotherapy group (51 vs 23 months); they considered that a relatively long interval between the initial PDAC resection and tumor relapse, with isolated and stable disease over time, and a favorable response to systemic chemotherapy indicated “good biology” [ 4 ].…”
Section: Discussionmentioning
confidence: 99%